Industrial-era decline in Arctic methanesulfonic acid is offset by increased biogenic sulfate aerosol. - Jongebloed, Ursula; Schauer, Andrew; Cole-Dai, Jihong; Larrick, Carleigh; Porter, William; Tashmim, Linia; Zhai, Shuting; Salimi, Sara; Edouard, Shana; Geng, Lei; Alexander, Becky (Proceedings of the National Academy of Sciences, 2023)
Marine phytoplankton are primary producers in ocean ecosystems and emit dimethyl sulfide (DMS) into the atmosphere. DMS emissions are the largest biological source of atmospheric sulfur and are one of the largest uncertainties in global climate modeling. DMS is oxidized to methanesulfonic acid (MSA), sulfur dioxide, and hydroperoxymethyl thioformate, all of which can be oxidized to sulfate. Ice core records of MSA are used to investigate past DMS emissions but rely on the implicit assumption that the relative yield of oxidation products from DMS remains constant. However, this assumption is uncertain because there are no long-term records that compare MSA to other DMS oxidation products. Here, we share the first long-term record of both MSA and DMS-derived biogenic sulfate concentration in Greenland ice core samples from 1200 to 2006 CE. While MSA declines on average by 0.2 µg S kg-1 over the industrial era, biogenic sulfate from DMS increases by 0.8 µg S kg-1. This increasing biogenic sulfate contradicts previous assertions of declining North Atlantic primary productivity inferred from decreasing MSA concentrations in Greenland ice cores over the industrial era. The changing ratio of MSA to biogenic sulfate suggests that trends in MSA could be caused by time-varying atmospheric chemistry and that MSA concentrations alone should not be used to infer past primary productivity.